Development of Agritourism Based on Seaweed Farming - I Gede Sumadi; Agung Suryawan Wiranatha (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
Nusa Penida Island in Bali has been known as one of popular touristdestinations in Bali. Despite of tourism, Nusa Penida Island waspopular because of the seaweed production. However, the seaweedproduction has declined in this island due to the domination oftourism development. During the Covid-19 pandemic, some peoplein this island have back to seaweed farming. This research aimed tofind out the potential of seaweed farming as an agritourism, and topropose development strategies for agritourism in this island. SuanaVillage was chosen as the location of this research because manyseaweed farming practices are still existed within this village area.Data was collected by using literature review, observation, interviews,and focus group discussion. Data analysis was undertaken by usingInternal-External Factor Analysis, IE Matrix, and SWOT Analysis.Research findings suggested that agritourism based on seaweedfarming at Suana Village has some positive supports in terms oftourist attractions, amenities, accessibility, and ancillary servicesavailable in this village. The IE Matrix analysis suggested that thegrand strategies for the seaweed agritourism development areproduct development and market penetration. It is also required improvement of human resources. This research results show that it is really important to build up competitiveness of development ofseaweed agritourism in order to link tourism and aquaculture inNusa Penida Island.